2012
DOI: 10.1002/jbm.a.34333
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteoinductivity and osteoconductivity through hydroxyapatite coating of silk‐based tissue‐engineered ligament scaffold

Abstract: Hybrid silk scaffolds combining knitted silk fibers and silk sponge have been recently developed for use as ligament-alone grafts. Incorporating an osteoinductive phase into the ends of a ligament scaffold may potentially generate an integrated "bone-ligament-bone" graft and improve graft osteointegration with host bone. To explore the possible application of hydroxyapatite (HA) coating in the fabrication of osteoinductive ends of silk-based scaffold, HA was coated on the hybrid silk scaffold and the effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 46 publications
1
72
0
Order By: Relevance
“…[36] He and coworkers further clarified that hydroxyapatite could act as nucleation sites for mineralization and promote further deposition of apatite crystals from cells, thus enhancing the formation of a mineral structure. [37] Several methods, including mass change method, scratch method, and alizarin red-based assay have been tried out to quantify the mineral contents. However, we were not successful since the microspheres were small, spherical, and the content of mineral was low.…”
Section: Discussionmentioning
confidence: 99%
“…[36] He and coworkers further clarified that hydroxyapatite could act as nucleation sites for mineralization and promote further deposition of apatite crystals from cells, thus enhancing the formation of a mineral structure. [37] Several methods, including mass change method, scratch method, and alizarin red-based assay have been tried out to quantify the mineral contents. However, we were not successful since the microspheres were small, spherical, and the content of mineral was low.…”
Section: Discussionmentioning
confidence: 99%
“…[ 66 ] Another report also showed that HAp coating on the silk scaffold resulted in an osteogenic differentiation of the seeded BMSCs in a normal culture medium, and this effect was further enhanced by culturing in osteogenic medium, indicating enhanced osteoinductivity of the HAp-coated silk scaffold. [ 128 ] Furthermore, recent in vivo studies also revealed the positive role of HAp incorporation in bone regeneration in defect models from small to large animals. [ 154,155 ] For instance, Liu et al demonstrated that nanofi brous hydroxyapatite/ chitosan (nHAp/CTS) scaffolds can promote bone regeneration by supporting the adhesion, proliferation, and activating integrin-BMP/Smad signaling pathway of BMSCs, when compared with the CTS group without HAp.…”
Section: Progress Reportmentioning
confidence: 98%
“…Such constructs have been explored for the engineering of tendon and ligaments tissue constructs [88]. Knitted scaffolds coated with hydroxyapatite have been utilized for engineering bone tissue and have shown excellent osteoconductivity [90]. Braided scaffolds formed from intertwined fibers offer the highest construct density and axial mechanical strength in comparison to those fabricated using other textile techniques.…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%